Meta Analisis Penerapan Model Problem Based Learning Dalam Meningkatkan Hasil Belajar IPA Siswa Sekolah Dasar - Tamariska Febri Kristiana; Elvira Hoesein Radia (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to determine how much influence the application of the Problem Based Learning model has in improving the science learning outcomes of elementary school students. Research with the title Problem Based Learning model in improving science learning outcomes has been done before. However, there is no further study regarding the results of research which is summarized and analyzes the effect of the application of Problem Based Learning in improving science learning outcomes. Data collection in this study was obtained by browsing journals from Google Scholar written by general authors and students. Keywords that are used to browse journals are: Problem Based Learning, science learning outcomes, elementary school. The data obtained is the result of research that has been done before which is then analyzed using a meta-analysis technique of influence or effect size. From the results of the analysis of 14 studies, the effect size calculation is 2.70 which indicates a high effect size value. Based on the results obtained, it can be concluded that the application of the Problem Based Learning model has a great influence in improving the science learning skills of elementary school students.